ECM Inspired Coating of Embroidered 3D Scaffolds Enhances Calvaria Bone Regeneration. (11th June 2014) - Rentsch, C.; Rentsch, B.; Heinemann, S.; Bernhardt, R.; Bischoff, B.; Förster, Y.; Scharnweber, D.; Rammelt, S.
Abstract : Resorbable polymeric implants and surface coatings are an emerging technology to treat bone defects and increase bone formation. This approach is of special interest in anatomical regions like the calvaria since adults lose the capacity to heal large calvarial defects. The present study assesses the potential of extracellular matrix inspired, embroidered polycaprolactone-co-lactide (PCL) scaffolds for the treatment of 13 mm full thickness calvarial bone defects in rabbits. Moreover the influence of a collagen/chondroitin sulfate (coll I/cs) coating of PCL scaffolds was evaluated. Defect areas filled with autologous bone and empty defects served as reference. The healing process was monitored over 6 months by combining a novel ultrasonographic method, radiographic imaging, biomechanical testing, and histology. The PCL coll I/cs treated group reached 68% new bone volume compared to the autologous group (100%) and the biomechanical stability of the defect area was similar to that of the gold standard. Histological investigations revealed a significantly more homogenous bone distribution over the whole defect area in the PCL coll I/cs group compared to the noncoated group. The bioactive, coll I/cs coated, highly porous, 3-dimensional PCL scaffold acted as a guide rail for new skull bone formation along and into the implant.